Reframing Student Mental Health and Well-Being in Post-Pandemic Education: A Global Opinion Grounded in Evidence - Isaac John Ibanga; Stephen Z. Kumazhege; Egunsola Abraham Olawuyi Emmanuel (Buletin Edukasi Indonesia, 2025)
The COVID-19 pandemic has profoundly reshaped global education systems, not only disrupting learning processes but also intensifying long-standing concerns regarding student mental health and well-being. This article offers an opinion-based scholarly analysis supported by contemporary literature to critically examine the escalating mental health challenges faced by students in the post-pandemic era. Key issues include the surge in anxiety and depression, heightened academic pressure, digital overload, and the growing prevalence of bullying and cyberbullying. Drawing upon global evidence, this paper argues that educational systems have been insufficiently responsive to the psychosocial dimensions of learning, particularly in contexts where stigma and limited institutional support persist. Using a conceptual framework that integrates individual, pedagogical, digital, and systemic factors, this article synthesizes empirical findings and policy discourses to illuminate structural gaps in current educational practices. The results and discussion are organized into three thematic sub-sections addressing post-pandemic mental health trends, digitalization-related stressors, and systemic barriers to student well-being support. The paper concludes by advocating for a paradigm shift toward holistic, inclusive, and culturally responsive mental health strategies within education, emphasizing the urgency of embedding psychosocial well-being as a core educational priority rather than a peripheral concern.